Waiting for Elijah : time and encounter in a Bosnian landscape - HadžiMuhamedović, Safet (Articulating journeys (Series), 2018)
"Waiting for Elijah is an intimate portrait of time-reckoning, syncretism and proximity in one of the world's most polarized landscapes, the Bosnian Field of Gacko. Centred on the shared harvest feast of Elijah's Day, the once eagerly awaited pinnacle of the annual cycle, the book shows how the fractured postwar landscape beckoned the return of communal life that entails such waiting. This seemingly paradoxical situation - waiting to wait - becomes a starting point for a broader discussion on the complexity of time set between cosmology, nationalism and embodied memories of proximity."--